Repositioning History for the Future - Recent Academic Debates in China - Eben von Racknitz, Ines (History compass, 2014)
Changes in the politics and society in post-Deng China are reflected in the research priorities of mainland Chinese university history departments, while questions of political legitimation in China and contact with colleagues abroad in the United States and Europe continue to generate new research topics. This article intends to show how several factors contribute to the shaping of historical research in China today. Ongoing developments in China will be demonstrated through two examples, namely the field of world history and the discussion surrounding New Qing history in China.